The Mutilated Face of World War I in Portugal - Correia,Sílvia (2017)
The disabled veterans of World War I take the paradoxical form of the mutilated hero. Portugals barely consensual participation in the European front of World War I turned disabled veterans into an inconvenient symbol to be neglected in the politically unstable post-war period. From the delay in official recognition to the slow collective mobilization, the disabled prove hard to analyze, whether because of the lack of sources or the difficulty in positioning them in a post-war era eager to celebrate and then quickly forget the vestiges of mutilated victory. This paper seeks to characterize the appearance of these men in public space and their consecration as victims of the states decision to go to war.